Dinamika Konflik Pendirian Rumah Ibadah (Studi Kasus Gereja Kristen Jawa Kanaan di Kecamatan Pondok Aren Kota Tangerang Selatan) - Aisyah, Siti Yeni (Inklusiva: Jurnal Studi Agama-Agama, 2023)
Religious conflict has always been a sensitive issue, especially regarding the establishment of houses of worship. The fulfillment of rights in religion is often hindered by majority-minority issues, in addition to concerns about the dissemination of religious doctrine also triggers rejection. This research wants to answer the question of how the dynamics of conflict over the establishment of houses of worship in Pondok Aren. This research is classified as a qualitative-case study using a sociological approach. Data collection methods are done through interviews, observation and literature study. The theory used borrows Ralf Dahrendorf's conflict theory. The results showed that there are several factors behind this conflict, namely: the lack of socialization about the rules of the establishment of houses of worship. Lack of communication between the two parties related to the establishment socialization. There is a third party interest. There are concerns from local residents about missionization. Although FKUB and the Police Chief have attempted to mediate, the resistance of the objectors is still an obstacle in resolving the conflict. Until now, the church is still in the process of completing licensing, while conditions in the field are conducive, although the objectors still maintain their opposition.